Establishment and maintenance of DNA methylation in nematode feeding sites - Bennett, Morgan; Hawk, Tracy E.; Lopes-Caitar, Valeria S.; Adams, Nicole; Rice, J. Hollis; Hewezi, Tarek (Frontiers in Plant Science, 2023)
A growing body of evidence indicates that epigenetic mechanisms, particularly DNA methylation, play key regulatory roles in plant-nematode interactions. Nevertheless, the transcriptional activity of key genes mediating DNA methylation and active demethylation in the nematode feeding sites remains largely unknown. Here, we profiled the promoter activity of 12 genes involved in maintenance and de novo establishment of DNA methylation and active demethylation in the syncytia and galls induced respectively by the cyst nematode Heterodera schachtii and the root-knot nematode Meloidogyne incognita in Arabidopsis roots. The promoter activity assays revealed that expression of the CG-context METHYLTRANSFERASEs is restricted to feeding site formation and development stages. CHROMOMETHYLASE1 (CMT1), CMT2, and CMT3 and DOMAINS REARRANGED METHYLTRANSFERASE2 (DRM2) and DRM3, which mediate non-CG methylation, showed similar and distinct expression patterns in the syncytia and galls at various time points. Notably, the promoters of various DNA demethylases were more active in galls as compared with the syncytia, particularly during the early stage of infection. Mutants impaired in CG or CHH methylation similarly enhanced plant susceptibility to H. schachtii and M. incognita, whereas mutants impaired in CHG methylation reduced plant susceptibility only to M. incognita. Interestingly, hypermethylated mutants defective in active DNA demethylation exhibited contrasting responses to infection by H. schachtii and M. incognita, a finding most likely associated with differential regulation of defense-related genes in these mutants upon nematode infection. Our results point to methylation-dependent mechanisms regulating plant responses to infection by cyst and root-knot nematodes.